Battle of the Centuries: The Roots of Arbitration Law Come from the 'Who Decides?' Controversy. Issue 10 (25th October 2021) - Samuel, Adam
Abstract : Although it was decided 56 years into the 19 th century, the real arbitration legacy of the 18 th century can be seen from the House of Lords decision in Scott v. Avery . The plaintiff insured his shop with the Newcastle A 1 Insurance Association and so became an association member. Association Rule 25 provided.